2008
DOI: 10.1021/jp804862w
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Effect on a Radical Pair Reaction as a Probe of Microviscosity

Abstract: The magnetic field effects (MFEs), caused by the ∆g mechanism, on the photoinduced hydrogen abstraction reaction of benzopheneone with thiophenol were investigated in alcoholic solutions of varying viscosities (η ) 0.55 to 59.2 cP) by a nanosecond laser flash photolysis technique. The escape yield of benzophenone ketyl radicals (Y) gradually decreased with increasing magnetic field strength (B) from 0 to 1.6 T. The relative yield observed at 1.6 T, R(1.6 T) ) Y(1.6 T)/Y(0 T), decreased with increasing η in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 63 publications
1
35
1
Order By: Relevance
“…In our previous paper, we estimated that the viscosity in the cage should be smaller than 5 cP from the results of the MFEs observed for the same reaction in alcoholic solutions. 17,23 These values are 1 order of magnitude smaller than the macroscopic viscosity of TMPA TFSA. Wishart and Castner et al reported that there are several microviscosities for ILs ranging from orders of magnitude smaller than the macroscopic viscosities to viscosities similar to or larger than the macroscopic viscosities.…”
mentioning
confidence: 94%
“…In our previous paper, we estimated that the viscosity in the cage should be smaller than 5 cP from the results of the MFEs observed for the same reaction in alcoholic solutions. 17,23 These values are 1 order of magnitude smaller than the macroscopic viscosity of TMPA TFSA. Wishart and Castner et al reported that there are several microviscosities for ILs ranging from orders of magnitude smaller than the macroscopic viscosities to viscosities similar to or larger than the macroscopic viscosities.…”
mentioning
confidence: 94%
“…This value is ten times smaller than that observed for the similar reaction between 3 BP Ã and PhSH (1:2 Â 10 8 s À1 mol À1 dm 3 ) although the viscosity is slightly higher (37.3 cP) than that of the present study. 10 Such a small rate constant of 3 TBP Ã may be due to the lower triplet energy of 3 TBP Ã (166 kJ mol À1 ) than that of benzophenone (290 kJ mol À1 ).…”
mentioning
confidence: 99%
“…In the present study, the self-quenching of 3 TBP Ã could successfully be suppressed in a viscous alcoholic solution of i-BuOH/c-HexOH, a SDS micellar solution, and an ionic liquid of TMPA TFSA. The reasons for suppressing the self-quenching of 3 TBP Ã may be as follows: high viscosity of the alcoholic solution, 10 cage effects with the high microviscosity of SDS micellar solution, [14][15][16][17] and cage effects with the low microviscosity of ionic liquid. 7,18,19 To elucidate the mechanism for suppressing the self-quenching, it is desirable to clarify the reaction field as a nanoscale structure.…”
mentioning
confidence: 99%
“…27 Studies on RIPs in mixed solvents have found evidence for the role of microheterogeneity in the solvent influencing the RP dynamics 28-31 and indeed MFEs have been used to measure solvent microviscosity in a range of solvents. 32 …”
Section: The Life Cycle Of a Radical Pairmentioning
confidence: 99%